Vertebral bone mineral measures and psychological wellbeing among individuals with Modic changes - Briggs, Andrew; O'Sullivan, Peter; Foulner, D.; Wark, J. (LA Press, 2012)
Purpose: This case-control pilot study examined whether vertebral bone mineral measures were associated with the presence of chronic low back pain (CLBP) and Modic changes (MCs), and to compare psychological wellbeing and inflammation among individuals with CLBP and MCs, compared to individuals with no history of low back pain and without MCs. Methods: Eleven individuals with MRI-defined MCs in the lumbar spine and CLBP (cases) and 10 individuals with no history of CLBP or MCs (controls) responded to standard questionnaires regarding pain characteristics and psychological health. Bone mineral density (BMD) was measured with postero-anterior and lateral-projection dual energy X-ray absorptiometry (DXA) to estimate areal BMD(aBMD) and apparent volumetric BMD (ap.vBMD). High sensitivity serum C-reactive protein (hsCRP) was measured as an index of inflammation. Results: While there was no difference between the groups in measures of depression, anxiety and stress, cases reported significantly greater pain catastrophizing attitudes (P <0.01). hsCRP concentrations did not differ between groups (P = 0.54). Among the 7 cases where MCs were identified between L3–4, significantly higher mean aBMD was observed at the affected vertebral level, compared to the adjacent, unaffected, cephalad level (P = 0.01–0.04), but not when ap.vBMD was calculated (P = 0.36). Conclusions: Vertebral BMD is not reduced among individuals with CLBP and MCs compared to a control group, although pain catastrophizing attitudes are increased among individuals with CLBP and MCs.